2013
DOI: 10.1155/2013/615857
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Posttraumatic Stress Disorder: A Systematic Review of Randomized Controlled Trials and Prospective Clinical Trials

Abstract: To evaluate the current evidence for effectiveness of acupuncture for posttraumatic stress disorder (PTSD) in the form of a systematic review, a systematic literature search was conducted in 23 electronic databases. Grey literature was also searched. The key search terms were “acupuncture” and “PTSD.” No language restrictions were imposed. We included all randomized or prospective clinical trials that evaluated acupuncture and its variants against a waitlist, sham acupuncture, conventional therapy control for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 32 publications
2
37
0
1
Order By: Relevance
“…The results of this review are comparable to the conclusion of the one previous systematic review on acupuncture for PTSD (Kim, Heo, et al, 2013). As with our review, this previous review concluded that evidence in support of acupuncture for PTSD is encouraging yet not cogent due to the small number of RCTs and participants providing data for meta-analyses.…”
Section: Other Reviews In This Areasupporting
confidence: 88%
See 2 more Smart Citations
“…The results of this review are comparable to the conclusion of the one previous systematic review on acupuncture for PTSD (Kim, Heo, et al, 2013). As with our review, this previous review concluded that evidence in support of acupuncture for PTSD is encouraging yet not cogent due to the small number of RCTs and participants providing data for meta-analyses.…”
Section: Other Reviews In This Areasupporting
confidence: 88%
“…A previous systematic review on acupuncture for PTSD concluded that, while encouraging, the evidence of effectiveness of acupuncture for PTSD was incomplete and required further high-quality RCTs (Kim, Heo, et al, 2013). However, this previous review was conducted prior to several recent RCTs on acupuncture for PTSD, included acupressure interventions in addition to needle acupuncture interventions, and did not examine possible moderators of the intervention.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison to other reviews A previous systematic review on the topic concluded that evidence in support of acupuncture for PTSD is encouraging yet not cogent due to the small number of studies providing data for their meta-analyses and limitations due to the methodological quality of included trials (Kim et al, 2013). The results of this review are compatible with this previous systematic review, though we are less encouraged by the current evidence base.…”
Section: Studysupporting
confidence: 74%
“…Several established psychological and pharmacological approaches for PTSD are supported by evidence from systematic reviews (Amos, Stein, & Ipser, 2014;Bisson, Roberts, Andrew, Cooper, & Lewis, 2013;Stein, Ipser, & Seedat, 2006). The most recent systematic review specifically on acupuncture for PTSD is four years old and was therefore conducted prior to several recent randomized controlled trials (RCTs) on acupuncture for PTSD (Kim et al, 2013). The review authors concluded that the evidence of effectiveness of acupuncture for PTSD is encouraging, yet they included uncontrolled clinical trials that provide less valid estimates of clinical effects, did not consider several important clinical outcomes such as depressive symptoms, quality of life, and sleep quality (Hollifield, 2011), did not analyze outcomes at different time points, and did not involve formal assessments of the quality of the body of evidence to indicate the degree of confidence in the accuracy of estimates of clinical effects.…”
mentioning
confidence: 99%